Primer registro de Syzygium jambos (Myrtaceae) naturalizada en Misiones, Argentina - Hurrell, Julio Alberto (2017)
Syzygium (Myrtaceae) is reported for the first time in Argentina: Syzygium jambos is described as a naturalized species in Misiones province. The genus is described, and a key for the cultivated species of Syzygium in Argentina are included. Also, data on distribution, phenology, pollination, dispersion, uses and reference material of the species, and comments on its naturalization are presented. This record is relevant given its status as an invasive plant in other parts of the world, in order to assess its future invasive potential.